Ingesting Stellera chamaejasme Significantly Impacts the Gastrointestinal Tract Bacterial Community and Diversity in Plateau Zokors (Eospalax baileyi) - Jialong Guo; Haijing Wang; Feng Jiang; Daoxin Liu (Microorganisms)
Intestinal bacteria are considered the “second genome” of the host, playing a crucial physiological role in assisting the host in degrading plant secondary compounds, nutrient absorption, immune regulation, and other aspects. To explore the effects of Stellera chamaejasme on the bacterial community of the gastrointestinal tract of plateau zokor, this study uses the 16S rRNA gene high-throughput sequencing technology, and the biodiversity and the community structure of gut bacteria in different gastrointestinal tract segments (the stomach and cecum) of plateau zokors. The results showed that at the phylum level, the dominant flora in the stomach and cecum of plateau zokors before and after ingesting Stellera chamaejasme were Firmicutes and Bacteroidetes. In plateau zokors that ingested Stellera chamaejasme, the relative abundance of Firmicutes in the stomach and cecum decreased, the relative abundance of Bacteroidetes increased, and the ratio of Firmicutes to Bacteroidetes decreased. After plateau zokors ingested Stellera chamaejasme, the ACE index demonstrated a significant reduction in the richness of the stomach bacterial community, while cecal bacterial community richness showed no significant change. Stellera chamaejasme exhibits significantly different effects on the bacterial communities in different segments of the gastrointestinal tract. Beta diversity analysis revealed that, after plateau zokors ingested Stellera chamaejasme, there were notable distinctions in the bacterial communities within both the stomach and cecum, alongside a marked reduction in the variability of the intestinal bacterial profiles across individuals. The results show that ingesting Stellera chamaejasme has a significant impact on the composition and structure of the gastrointestinal tract bacterial community in plateau zokors.